Optimal Defaults with Normative Ambiguity - Goldin, Jacob; Reck, Daniel (The Review of Economics and Statistics, 2022)
Default effects are pervasive, but the reason they arise is often unclear. We study optimal policy when the planner does not know whether an observed default effect reflects a welfare-relevant preference or a mistake. Within a broad class of models, we find that determining optimal policy is impossible without resolving this ambiguity. Depending on the resolution, optimal policy tends in opposite directions: either minimizing the number of nondefault choices or inducing active choice. We show how these considerations depend on whether active choosers make mistakes when selecting among nondefault options. We illustrate our results using data on pension contribution defaults.